Overgrowth of gold nanorods by using a binary surfactant mixture - Khlebtsov, Boris N (Langmuir : the ACS journal of surfaces and colloids, 2014)
Seed-mediated surfactant-assisted growth is widely used as the most effective method for gold nanorod (NR) synthesis. Using prepared nanorods as seeds for further overgrowth can increase the dimensional tunability of the final particles. However, overgrowth in usual cetyltrimethylammonium bromide (CTAB) surfactant solutions leads to poor control of the final particle shape and size. In this work, we report an improved strategy to demonstrate the controllable overgrowth of gold NRs in the binary surfactant mixture sodium oleate (NaOL) + CTAB. This approach overcomes the difficulty of growing NR suspensions with small amounts of impurities. By controlling the total amount of added NR seeds, it is possible to tune the average length, diameter, and plasmon resonances of overgrown particles in a wide range. Together with the original NaOL + CTAB method developed by Murray and co-workers ( Nano Lett. 2013 , 13 , 555 ), this overgrowth approach expands the dimensional and plasmonic tunability of the fabrication technology without any decrease in the monodispersity and purity of samples